Effect Of Probiotic Supplementation On Milk Yield And Its Composition In Buffaloes (Bubalus Bubalis) - Tewari, Dharmesh; Jain, R.K.; Patil, Nagendra; Mudgal, Vishal; Haq , Zulfqar ul (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The study on effect of probiotic supplementation on milk yield showed that the average daily milk yield was higher (P
Keywords: Lactobacillus; Saccharomyces; Milk production; Milk composition; buffaloes